2017
DOI: 10.1007/s00296-017-3844-9
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib improves atherosclerosis despite up-regulating serum cholesterol in patients with active rheumatoid arthritis: a cohort study

Abstract: Patients with rheumatoid arthritis (RA) have an increased cardiovascular (CV) risk. This study aimed to analyze the effects of Tofacitinib treatment, a Janus kinase inhibitor, on atherosclerosis in patients with RA. Patients with an active RA (28-joint disease activity score-erythrocyte sedimentation rate > 3.2) despite methotrexate (MTX) treatment 12 mg/week were included in this open-label prospective study and started on Tofacitinib (10 mg/day, 5 mg twice/day). Japanese guideline does not allow high dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 39 publications
1
31
2
2
Order By: Relevance
“…Whether these changes increase the risk of cardiovascular disease is also unclear . In fact, jakinibs may limit vascular damage in patients with autoimmune disease despite increasing cholesterol …”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these changes increase the risk of cardiovascular disease is also unclear . In fact, jakinibs may limit vascular damage in patients with autoimmune disease despite increasing cholesterol …”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
“…151,152 In fact, jakinibs may limit vascular damage in patients with autoimmune disease despite increasing cholesterol. 153 In April 2017, the US FDA expressed concern about thromboembolic events (deep venous thrombosis and pulmonary embolism) observed in clinical trials of baricitinib in RA. The European and Japanese labels for baricitinib were recently updated to include a precaution related to potential thromboembolic events in patients at risk, but the extent to which this complication is a significant risk for jakinibs in general needs further assessment, 154 particularly as many cause thrombocytopenia through their ability to inhibit TPO.…”
Section: Hematological and Cardiovascular Effectsmentioning
confidence: 99%
“…However, the role of these agents in the modulation of cardiovascular risk remains undetermined 15 16. Limited evidence suggested that tofacitinib-based therapy positively modifies the risk of cardiovascular disease,17 18 while a growing body of literature indicated that Jakinibs adversely affect several cardiovascular risk factors (such as serum lipid profile and platelet count) and potentially increase thrombotic risk which directly leads the US Food and Drug Administration (FDA) to restrict approval to only 2 mg baricitinib 19–22. Additionally, in upadacitinib premarketing trials, major adverse cardiovascular events (MACEs) continuously reported in patients with RA receiving upadacitinib has further generated cardiovascular concerns 23…”
Section: Introductionmentioning
confidence: 99%
“…Tofacitinib improved ED in AIA and to investigate whether the bene ts of Tofacitinib on ED translate into a reduction of CV events in RA patients. Supporting this hypothesis, Tofacitinib tended to reduce carotid intima-media thickness in a small cohort of RA patients (43).…”
Section: Discussionmentioning
confidence: 73%